The Intake of Yogurt With Omega-3 Fatty Acids Affects Bone Quality in Growing Wistar Rats. Influence of Previous Nutritional Status - Godoy, Maria Fernanda (2023)
Publicado en: Current Developments in Nutrition 7, Supplement 1 : 100536. (July 2023)